The effects of fatigue on sprint and COD mechanics and its relationship with HSI - Alcaraz, P. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Hamstrings strain injury (HSI) is the most common injury in intermittent running sports such as Australian football, American football, rugby, and football (soccer) (Jones et al., 2019; Mack et al., 2020; Opar, Williams, & Shield, 2012; Orchard et al., 2020; Prieto-Lage, Louzao-Neira, Argibay-González, & Gutiérrez-Santiago, 2020; Ribeiro-Alvares et al., 2019). This type of injury is characterized by acute pain in the posterior thigh with disruption of the hamstrings muscle fibres, where direct external contact with the thigh is excluded as a cause of injury (Liu, Garrett, Moorman, & Yu, 2012; Opar et al., 2012; Poudel & Pandey, 2020). Injury rates are particularly high in football, accounting for 37% of all muscle related injuries (Ekstrand, Hägglund, & Waldén, 2011), and the recurrence rate is also remarkably high (Ekstrand et al., 2020; Martin Hägglund et al., 2013; Heiderscheit, Sherry, Silder, Chumanov, & Thelen, 2010; Woods et al., 2004).Thus, minimizing the risk of first injury is considered a key aspect of overall hamstrings injury reduction strategies. Despite the increasing research focus in this area, the potential injury mechanisms are not well defined (Sun et al., 2015) and injury incidence seems to have increased (Eirale, 2018; Ekstrand, Waldén, & Hägglund, 2016; Martin Hägglund et al., 2013) in recent years One factor that is known to critically affect injury risk is the level of neuromuscular fatigue (Huygaerts et al., 2020; Lehnert et al., 2017). This fatigue may result from either acute, residual (recovery from competition or training) or chronic physical exercise burden. Epidemiological evidence for an influence of acute fatigue is provided by data showing higher injury rates towards the late stages of a football game (Ekstrand et al., 2011). The accumulation of fatigue across training and competition periods is also linked to injury risk, especially when abrupt increases in total training loads, intensities or high speed running are observed (Green, Bourne, van Dyk, & Pizzari, 2020) or when match density is high, allowing only short recovery between competitive play (Calleja-Gonzalez et al., 2020). However, acute and chronic neuromuscular fatigue might influence risk in very different ways and since player monitoring practices, which are commonly performed and considered a cornerstone of player welfare systems (Matinlauri, Alcaraz, et al., 2019; Taberner & Cohen, 2018), should reduce the risk of chronic fatigue-related injury risk, the current presentation will focus predominately on neuromuscular factors that might trigger an acute hamstring injury event. Specifically, since the majority of HSI occur at maximal or near-maximal running speeds (Sugiura, Sakuma, Sakuraba, & Sato, 2017), the present presentation will describe how acute fatigue could affect mechanical and neuromuscular variables during high-speed running and Change of Directions.